2017
DOI: 10.1097/md.0000000000007462
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac metastasis of tongue squamous cell carcinoma complicated by pulmonary embolism

Abstract: Rationale:Cardiac metastasis is known as a rare complication of head and neck malignancy.Patient concerns:We present a 58-year-old woman patient with a history of tongue carcinoma who was admitted in emergency department for sudden chest pain. Imaging work-up by computed tomography (CT) and positron emission tomography-computed tomography (PET-CT) diagnosed a cardiac metastasis complicated by intraventricular thrombus and pulmonary embolism.Diagnosis:Cardiac metastasis from tongue carcinoma complicated by pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…18 When diagnosed ante-mortem, patients may present with nonspecific cardiac symptoms such as chest pain, shortness of breath, and palpitations. 19 In this systematic review, patients commonly demonstrated nonspecific cardiac symptoms such as chest pain, shortness of breath, syncope, and weight loss. Of these symptoms, chest pain and shortness of breath were the most prevalent (29.0% of cases), followed by syncope, then weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…18 When diagnosed ante-mortem, patients may present with nonspecific cardiac symptoms such as chest pain, shortness of breath, and palpitations. 19 In this systematic review, patients commonly demonstrated nonspecific cardiac symptoms such as chest pain, shortness of breath, syncope, and weight loss. Of these symptoms, chest pain and shortness of breath were the most prevalent (29.0% of cases), followed by syncope, then weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…With ECG changes being nonspecific, radiologic imaging like CT chest and cardiac MRI are relevant and have better precision. Echocardiography may be useful in assessing the functional impairment associated with the mass …”
Section: Discussionmentioning
confidence: 99%
“…Head and neck cancers with cardiac metastasis are very rare and are uniformly fatal, with a maximum reported survival of 3 months . Here we present a case of a patient with cardiac metastasis from soft palate primary disease who has survived for more than 18 months.…”
mentioning
confidence: 95%
“…The incidence of cardiac metastases is substantially higher in malignancies from other sites such as melanoma, lung, breast, esophagus, and lymphomas. Local recurrences are more common for head and neck tumors, however, when distant metastases occur, they often involve the lung, skin, liver or bone [1,2]. Due to the nonspecific symptoms associated with cardiac metastases, they are often not detected until an advanced stage or at autopsy; thus, the reported incidence has varied widely in the literature from 0.2% to 11.8% [1,3].…”
Section: Introductionmentioning
confidence: 99%